2015
DOI: 10.1161/strokeaha.114.007286
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Study of Intracranial Aneurysms

Abstract: Background and Purpose-Rupture of intracranial aneurysms (IAs) causes subarachnoid hemorrhage, leading to immediate death or severe disability. Identification of the genetic factors involved is critical for disease prevention and treatment. We aimed to identify the susceptibility genes for IAs. Methods-Exome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
0
36
1
Order By: Relevance
“…Yan et al (2015) had broader inclusion criteria and sequenced families with three or more affected first- to third- degree relatives. They sequenced 42 affected people from 12 families of Japanese ancestry.…”
Section: Next-generation Sequencing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al (2015) had broader inclusion criteria and sequenced families with three or more affected first- to third- degree relatives. They sequenced 42 affected people from 12 families of Japanese ancestry.…”
Section: Next-generation Sequencing Studiesmentioning
confidence: 99%
“…While both of these protein changes are predicted to be deleterious, relatively little is known about the gene function and there was not sufficient evidence to classify either mutation as pathogenic. Yan et al (2015) then selected ten variants from nine genes, based on functions that were plausibly associated to the pathogenesis of intracranial aneurysms, for Sanger sequencing and replication in two additional Japanese cohorts. The first replication cohort consisted of probands from 24 independent FIA families, and the second replication cohort included 426 individuals diagnosed with sporadic IBA.…”
Section: Next-generation Sequencing Studiesmentioning
confidence: 99%
“…Rupture of IAs can cause subarachnoid hemorrhage, which has a high ratio of fatality and morbidity [3]. Although several genome-wide association studies have been performed worldwide [47], the pathogenesis of IAs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Known risk factors for aneurysm formation include hypertension, smoking, and alcohol consumption; however, familial occurrences and an association with heritable connective tissue diseases-including polycystic kidney disease, and neurofibromatosis type 1-has been established, supporting a genetic component. Recently, Yan et al [7] reported that the ADAMTS15 gene may be a strong candidate for familial aneurysm etiology.…”
Section: Discussionmentioning
confidence: 99%